Complete chloroplast genome of the medicinal herb Veronicastrum axillare (Sieb. et Zucc.) Yamazaki and the phylogenetic relationship analysis within the tribe Veroniceae. Issue 5 (4th May 2022) - Luo, Jiawen; Gong, Qiuyi; Zhou, Manjia; Liu, Qiang; Cheng, Rubin; Ge, Yuqing
Abstract: Veronicastrum axillare (Sieb. et Zucc.) Yamazaki is a traditional medical plant with versatile biological activities. Here, we reported the complete chloroplast genome sequence of V. axillare with a total length of 152, 691 bp, containing two IR regions of 25, 765 bp each, an LSC region of 83, 559 bp, and an SSC region of 17, 602 bp. The genome encodes 131 genes, including 85 protein-coding genes, 37 tRNAs, eight rRNAs, and one pseudogene ( ycf1 ). The overall GC content is 38.3%, with the highest content of 43.31% in IR region. Comparative analysis revealed 4 potential hotspots among V. axillare and other Veroniceae plants, providing potential markers for population investigations in the tribe Veroniceae. A total of 56 simple sequence repeats were identified in V. axillare. Phylogenetic analysis indicated a sister relationship between V. axillare and V. sibiricum, suggesting a close genetic relationship between the two Veronicastrum species. Our results provide basic genetic resources for investigating the evolutionary status of V. axillare within the tribe Veroniceae.